THREE TALAQ AT ONCE IN DIVORCE ACCORDING TO THE UNDERSTANDING OF HADITH - Suryani, Suryani (IBLAM LAW REVIEW, 2022)
Marriage life is a goal that is highly prioritized in Islam. However, at a time in human life when it is impossible to continue a close relationship with one's partner, then what is the goal of marriage ends in the middle of the road and divorce occurs. This research This research is a type of library research. Data sources are fiqh books, books, and studies in various media that discuss triple talaq at once. The data analysis technique in this research is qualitative with deductive reasoning, namely a thinking method that applies general things first to be connected in specific parts. Triple talaq is a type of talaq that cannot be referred to and cannot be remarried unless the marriage takes place after the ex-wife marries someone else and then a ba'daldukhul divorce occurs and the iddah period ends. In Jurisprudence, if the husband has uttered the word talaq even outside the court against the wife then it is said that talaq has occurred. Triple talaq at once, when viewed in the current context, tends to be less relevant, because the current talaq must go through a judicial process and procedure.